Greening the Greyfields New Models for Regenerating the Middle Suburbs of Low-Density Cities - Newton, Peter W.; Newman, Peter W.G; Glackin, Stephen; Thomson, Giles (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This open access book outlines new concepts, development models, governance and implementation processes capable of addressing the challenges of transformative urban regeneration of cities at precinct scale.